Adsorption behaviour of copper and gold Glycinates in alkaline media onto activated carbon. Part 2: Kinetics - Tauetsile, P.; Oraby, Elsayed; Eksteen, Jacques (Elsevier, 2018)
The kinetics for the competitive adsorption of gold and copper onto activated carbon from synthetic alkaline glycine solutions was studied. The adsorption rate for both gold and copper at the initial stage was modelled using the Fleming k,n adsorption kinetic model. The coefficient of variation (R 2 ) of the model were close to unity for both gold and copper adsorption data. The effects of pH, free glycine, ionic strength, initial gold and copper concentrations and carbon concentration were assessed on the adsorption kinetics of these two metals. The results showed that > 98% of gold was adsorbed onto activated carbon in 6 h or less under all studied conditions. According to the adsorption tests results, carbon concentration is the only parameter that significantly affected the initial gold adsorption rate. For all other studied parameters, the initial adsorption rate is quite robust, with a few variations in process conditions only affecting it slightly. Activated carbon was found to be very selective for gold glycinate complexes over copper glycinates, with over 99.0% gold adsorbed in 24 h and < 15% copper adsorbed in the same duration under optimum conditions from a solution containing 2 ppm gold and 40 ppm copper.